E-CDCCText Development: An Instructional Material for Facilitating Conceptual Change in Fluid Concepts - Nurdini, Nurdini; Suhandi, Andi; Fratiwi, Nuzulira Janeusse; Samsudin, Achmad; Ramalis, Taufik Ramlan; Feranie, Selly (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Effective instruction of fluid concepts in physics requires a deep understanding of students' preconceptions and the implementation of pedagogical strategies that promote conceptual change. This study aims to develop the Electronic Conceptual Development and Conceptual Change Text (E-CDCCText), a digital instructional resource designed to foster conceptual change in students’ understanding of fluid mechanics. Employing the Design and Development Research (DDR) methodology, the development followed the ADDIE model. Validation by five expert reviewers, supported by analysis using Facet software, confirmed the material’s quality in terms of content accuracy, structural coherence, narrative clarity, and media design. The E-CDCCText comprises seven structured sections that guide students through a systematic process of constructing and reconstructing scientific concepts, integrating both conceptual development and conceptual change frameworks. The content targets three core fluid concepts: hydrostatic pressure, buoyant force, and the principles underlying floating, suspending, and sinking. The implementation phase involved 64 tenth-grade students, whose conceptual understanding was assessed using a validated four-tier diagnostic test. Results demonstrated a significant enhancement in students’ scientific conceptions, indicating the efficacy of the E-CDCCText in reducing misconceptions. In conclusion, the E-CDCCText is a validated and effective digital instructional tool for supporting conceptual change and improving students’ understanding of fluid concepts in physics education.Keywords: conceptual change, E-CDCCText, fluid concept, instructional material